‘FUNCTIONAL WRITING' AS A SOCIAL ACT: SFL INFORMED GENRE-BASED APPROACH IN TEACHING EFL WRITING TO PRE-SERVICE TEACHERS - Rahayu, Nurhadianty; Musyarofah, Siti Ulfa (ENGLISH JOURNAL, 2022)
The study explores how Systemic Functional Linguistics (SFL)-informed Genre-Based Approach (GBA) to teaching English as a Foreign Language writing is orchestrated in a teacher training program. This approach helps student teachers see the socio-communicative consequences of their metalinguistic repertoires to achieve certain communicative purposes to a particular readership. The data are collected through students' writing and their reflection about learning writing instructed by SFL-informed GBA. The data analysis is done using Halliday Systemic Functional Linguistics to see whether texts include appropriate lexicogrammatical choice to represent text as a social semiotic means. Results show that students are aware of their socio-communicative means of writing for a certain readership. The implementation of GBA may affect students' awareness of writing as a social act, yet a more comprehensive study needs to be developed to see how SFL-informed GBA affects pre-service teachers writing and how it helps shape English as a Foreign Language (EFL) teaching in their own classrooms.